The impact of new digital infrastructures on urban carbon emissions-An empirical study from Chinese cities - Wang, Yongkai; An, Qiguang; Xie, Qian; Wang, Ruoyu (Frontiers in Environmental Science, 2024)
Introduction In the digital era, new digital infrastructures (NDIs) play a pivotal role in fostering economic growth and technological innovation. However, their ecological impact, particularly on carbon dioxide emissions, remains underexplored. Addressing this gap holds significant practical and theoretical value. Methods Utilizing panel data from 283 Chinese cities spanning 2009 to 2020, this study employs a two-way fixed-effects model to empirically assess the influence of NDIs on urban carbon emissions (UCE). Additionally, a mediation effect model is used to examine the mechanisms of this influence. Results The findings reveal that: (1) NDIs significantly mitigate UCE levels, a conclusion supported by robustness tests involving instrumental variables and the exogenous policy shocks of smart city pilot programs; (2) NDIs primarily impact UCE through two channels: the digital economy and green technology innovation; and (3) heterogeneity analysis indicates that NDIs predominantly curb carbon emissions in cities with lower administrative levels, while positively contributing to UCE intensity in higher administrative level cities. Notably, NDIs substantially reduce UCE in non-old industrial cities, with a negligible effect in old industrial cities. Discussion This research expands the understanding of the economic-environmental implications of NDIs, offering valuable insights for policymakers regarding NDIs’ environmental impacts. It also provides strategic guidance for urban low-carbon transitions in the big data era.